Polymeric Immunoglobulin Receptor Mediates Immune Excretion of Mucosal IgM–Antigen Complexes Across Intestinal Epithelium in Flounder (Paralichthys olivaceus) - Sheng, Xiuzhen; Qian, Xiaoyu; Tang, Xiaoqian; Xing, Jing; Zhan, Wenbin (Frontiers in Immunology, 2018)
Polymeric immunoglobulin receptor (pIgR) is one important player of mucosal defenses, but very little is known on pIgR-mediated immune excretion of the antigens that penetrate mucosal surface in fish. Previously we cloned the pIgR of flounder (Paralichthys olivaceus) and developed anti-pIgR antibody. In this study, the flounders were immunized intraperitoneally with the chicken ovalbumin (OVA) and the control protein bovine serum albumin (BSA) to elicit mucosal IgM antibody and pIgR response, and then challenged with OVA via caudal vein injection after the immunized OVA was absent from fish body at the fourth week post immunization. After OVA challenge, strong OVA-positive fluorescence signals were observed in submucosa, lamina propria and epithelial cells of the hindgut at 30 min, increased proceeding towards the distal portion of intestinal folds, reached a peak at 2-3 h and then weakened and disappeared at 12 h, indicating that the OVA rapidly diffused from bloodstream into submucosa and lamina propria and excreted across intestinal epithelium. Whereas in BSA-immunized and OVA-challenged control fish, the OVA was detected in lamina propria but not in intestinal epithelium due to the lack of OVA-specific antibody. Accordingly, in intestinal epithelium, the transepithelial transport of OVA was confirmed by immunogold electron microscopy, and co-localization of OVA, IgM and pIgR were illuminated by multiple-label immunofluorescence confocal microscopy. Furthermore, in gut mucus but not in serum, a ~800kDa protein showed IgM-positive, OVA-positive and pIgR-positive simultaneously, and the OVA, together with IgM and secretory component (SC) of pIgR, could be immunoprecipitated by anti-OVA antibody, demonstrating the existence of SC-polymeric IgM-OVA complexes. All these results collectively revealed that the pIgR could transport mucosal IgM-OVA complexes from lamina propria across intestinal epithelium into gut mucus via the transcytosis in flounder. These new findings provided direct evidences for pIgR-mediated immune excretion of IgM-antigen complexes, and better understanding the role of pIgR in mucosal immunity in teleost fish.